2009
DOI: 10.1164/rccm.200810-1596oc
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Acute Exacerbations of Idiopathic Pulmonary Fibrosis

Abstract: Rationale: The molecular mechanisms underlying acute exacerbations of idiopathic pulmonary fibrosis (IPF) are poorly understood. We studied the global gene expression signature of acute exacerbations of IPF. Objectives: To understand the gene expression patterns of acute exacerbations of IPF. Methods: RNA was extracted from 23 stable IPF lungs, 8 IPF lungs with acute exacerbation (IPF-AEx), and 15 control lungs and used for hybridization on Agilent gene expression microarrays. Functional analysis of genes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
254
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(281 citation statements)
references
References 53 publications
17
254
1
9
Order By: Relevance
“…The results described herein suggest a novel mechanism by which influenza infection can induce epithelial cell death and promote collagen deposition, which are critical steps in exacerbations of pulmonary fibrosis (25). This further raises the possibility that TLR3 activation by multiple RNA viruses may increase TGF␤ activity in epithelial cells and define a mechanism through which viral infection may initiate acute exacerbations of fibrotic lung disease.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The results described herein suggest a novel mechanism by which influenza infection can induce epithelial cell death and promote collagen deposition, which are critical steps in exacerbations of pulmonary fibrosis (25). This further raises the possibility that TLR3 activation by multiple RNA viruses may increase TGF␤ activity in epithelial cells and define a mechanism through which viral infection may initiate acute exacerbations of fibrotic lung disease.…”
mentioning
confidence: 67%
“…Our data suggest that lung collagen can be deposited in the lung of virally infected mice as early as 5 days post-infection. Although we are not proposing that influenza infection causes pulmonary fibrosis, it is evident that key mechanisms involved in the development of fibrosis, including ␣v␤6-mediated TGF␤ activation (4,68), epithelial apoptosis (25), and lung collagen deposition (69), are triggered by influenza infection and may thus promote fibrogenesis in an appropriately susceptible host. In conclusion, the results described herein provide a novel mechanism through which pulmonary infection with influenza virus can result in the activation of TGF␤ via a Smad3-, TLR3-, and ␣v␤6 integrin-dependent pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Recent data have suggested that AE-IPF may be due to an acceleration of the underlying fibroproliferative disease process (Konishi et al 2009;Collard et al 2007). Finding higher pulmonary expression of HSP47, a collagen-specific molecular chaperone, in DAD than in UIP tissues in this study is consistent with that hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have suggested that AE-IPF may be due to an acceleration of the underlying fibroproliferative disease process (Konishi et al 2009;Collard et al 2007); it is therefore assumed that HSP47 is also involved in its pathogenesis. Previous studies in several experimental animal fibrosis models have shown that downregulation of HSP47 expression reduces production of collagen and subsequently diminishes progression of fibrosis (Sunamoto et al 1998;Nishino et al 2003;Hagiwara et al 2007a, b, c;Obata et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-3 gene expression was further assessed by real-time quantitative PCR as described previously. 14 Total protein from the lung tissue was extracted with Pierce T-PER tissue protein extraction reagent (Thermo Fisher Scientific, Rockford, IL) according to the manufacturer's protocol. Western blot analysis of human tissue specimens for MMP-3 was performed as described previously.…”
Section: Human Lung Microarray Analysismentioning
confidence: 99%